Gut microbiota targeted nanomedicine for cancer therapy: Challenges and future considerations. (January 2021) - Riaz Rajoka, Muhammad Shahid; Mehwish, Hafiza Mahreen; Xiong, Yongai; Song, Xun; Hussain, Nazim; Zhu, Qinchang; He, Zhendan
Abstract: Background: Nanomedicine has become one of the most promising technologies to modernize the traditional food. However, not only the public perception of the new technology is uncertain, but also the regulators have not yet to agree on rules that apply globally. The gastrointestinal tract microbiota and its genes (the microbiome) are considered a fundamental part of the human body. The gut microbiota is a major part of the host microbiota and contains approximately 3 × 10 13 bacterial cells in a commensal relationship with the host. However, once the gastric ecosystem is altered, various bacterial species (e.g., antibiotic-resistant Enterococcus and Clostridium difficile ) can increase and develop pathogenic phenotypes. Recent evidence suggests that the gut microbiota is involved in carcinogenesis and can enhance the activity, efficacy, and toxicity of anticancer therapies. Recently, there is fast-growing concern regarding the effect of nanoparticles on the human gut microbiota. Nanomaterials can enter the human body via skin contact, ingestion, and inhalation. Scope and approaches: In the present review, the recent advances on the roles of microbiota and nanomaterials in cancer therapy, the microbiota and their metabolic interventions via nanomaterials, microbial inspiration via nanomaterials, and the challenges associated with using nanomaterials in humans and animals is discussed. In short, this review will focus on the current status and future perspectives of gut microbiota targeted nanotechnology for cancer therapy and cancer-related metabolic diseases. Key findings and conclusions: The changes in the gut microbiota or microbiome play vital roles in human diseases such as cancer. Traditional microbiome treatments have led to improved cancer treatments in some cases; however, problems such as collateral injury to the symbiotic microbiome and reliability of these treatment methods have led to new technological developments designed specifically for cancer microbiota crossing point. Hence, the prosperousness of nanomaterials in cancer prevention has led to the idea that nanomaterials can alter the cancer-causing microbiome/microbiota and their metabolites as well as alter the cancer microenvironment. Therefore, nanomaterials can be used as novel strategies to treat cancer. However, this emerging research area requires further in vivo clinical trials to determine the exact mechanisms of action involved in treating cancer via nanomaterials. Further studies should explore the connection between nanomaterials, the microbiota, microbial metabolites, cancer and cancer-related microenvironments in animals and humans. Graphical abstract: Image 1 Highlights: Increasing evidence suggested that the gut microbiota dysbiosis influence cancer. Interaction between nanomaterials and gut microbiota are largely unexplored. The concept of nanomedicine based approached to alter gut microbiota for cancer therapy has been proposed. The gut microbiota and nanomedicine might provide new specific biomarkers for cancer therapy. Future perceptive toward the development of novel nanomedicine for cancer therapy are discussed.